1975
DOI: 10.3133/pp852
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Platoro caldera complex and related volcanic rocks, southeastern San Juan Mountains, Colorado

Abstract: Volcanic rocks in the San Juan Mountains constitute the largest erosional remnant of a once nearly continuous volcanic field that extended over much of the southern Rocky Mountains and adjacent areas in Oligocene and later time. Recent regional studies have shown that the gross petrologic evolution of the San Juan remnant of this field was relatively simple, beginning with intermediate-composition lavas and breccias, followed closely in time by more silicic ash-flow tuff, and ending with a bimodal association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
214
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(220 citation statements)
references
References 37 publications
6
214
0
Order By: Relevance
“…Whereas the general model of ash-flow eruption and caldera development (Ratte and Steven, 1964;Smith and Bailey, 1968;Lipman, 1975;Steven and Lipman, 1976;Bailey and others, 1976) was applied to studies of both areas, the results were quite different. Minor differences in timing and conditions of eruption led to strongly contrasting volcanic accumulations and structures; depth and configuration of the source magma chambers may have had a major controlling influence.…”
Section: Evolution Of the Mount Belknap And Red Hills Calderasmentioning
confidence: 93%
“…Whereas the general model of ash-flow eruption and caldera development (Ratte and Steven, 1964;Smith and Bailey, 1968;Lipman, 1975;Steven and Lipman, 1976;Bailey and others, 1976) was applied to studies of both areas, the results were quite different. Minor differences in timing and conditions of eruption led to strongly contrasting volcanic accumulations and structures; depth and configuration of the source magma chambers may have had a major controlling influence.…”
Section: Evolution Of the Mount Belknap And Red Hills Calderasmentioning
confidence: 93%
“…Adjacent to, and partly within the southwestern part of the study area, is the Jasper district, where there are several small mines and prospect pits in gold, silver, lead, and zinc-bearing veins, though it is not known what production occurred there . All of these altered and mineralized regions occur at intersections between the northwesttrending Pass Creek fault zone and ring fracture zones of the Platoro and Summitville calderas (Lipman, 1975). A widespread zone of sporadic alteration and pyritization not associated with this structural setting occurs with the Cat Creek stock in the southern part of the study area.…”
Section: Mining Districts Mines and Mineral Occurrencesmentioning
confidence: 99%
“…A widespread zone of sporadic alteration and pyritization not associated with this structural setting occurs with the Cat Creek stock in the southern part of the study area. There are numerous prospect pits and adits here, but production is not known (Lipman, 1975). There are no other areas of mineralization or alteration within the study area.…”
Section: Mining Districts Mines and Mineral Occurrencesmentioning
confidence: 99%
“…The Alamosa River stock, of monzonitic composition, was emplaced at 29.1 ± 1.2 MYBp into predominantly andesitic volcanics forming and filling caldera structures (Lipman, 1975). The La jara is predominantly a densely welded and devitrified ash flow tuff primarily of phenocryst rich quartz latite, ejected by an explosive event at 29.8 ±1.2 MYBP.…”
Section: Introductionmentioning
confidence: 99%
“…Based on analyses of oxygen isotope ratios in 260 minerals and whole rock samples from the Alamosa River stock region, Williams (1980) suggested that the heat from the stock and other small intrusions, which range in age from 28 to 22.8 MY (Lipman, 1975) , Initiated extensive hydrothermal circulation. A roughly concentric aureole of S 18g depletion was noted around the south and east margins of the stock, with depletion enhanced along two major faults, attesting to the importance of fracture permeabil ity in the circulation of this system.…”
Section: Introductionmentioning
confidence: 99%